A review on furan: Formation, analysis, occurrence, carcinogenicity, genotoxicity and reduction methods. Issue 3 (4th February 2021) - Batool, Zahra; Xu, Dan; Zhang, Xia; Li, Xiaoxi; Li, Yuting; Chen, Zhiyi; Li, Bing; Li, Lin
Abstract: Furan (C4 H4 O) is a volatile, heterocyclic and carcinogenic heterocyclic chemical compound occurring in a wide range of thermally processed foods. Several studies have been conducted to analyze the formation conditions, triggering furan formation via model systems. Furan can be encountered via various pathways including thermal degradation, oxidation of polyunsaturated fatty acids, thermal rearrangement of carbohydrates in the presence of amino acids, thermal degradation of certain amino acids. Furan has been proven to cause cancer in experimental animal models and classified as a possible human carcinogen by International agency for research on cancer based on sufficient evidences. Thus, different strategies should be developed to reduce furan contents in commercially available food stuffs while food processing. This review summarizes some current evidences of furan formation from different precursors, analytical methods for its detection, and its toxicity that might lead to carcinogenicity and genotoxicity with human risk assessment. In addition, furan occurrence in different thermally processed foods entailed by several recent studies as well as furan mitigation strategies during food processing have also been illustrated in this review.